Stand structure adjustment influences the biomass allocation in naturally generated Pinus massoniana seedlings through environmental factors - He, Wenchun; Wang, Yu; Wang, Xiao; Wen, Xiaochen; Li, Tianyi; Ye, Mengting; Chen, Gang; Zhao, Kuangji; Hou, Guirong; Li, Xianwei; Fan, Chuan (Frontiers in Plant Science, 2022)
The natural regeneration of seedlings is a key factor for forest succession. Nevertheless, researches on explaining the mechanism of the growth and photosynthesis allocation of the regenerated seedlings after disturbing are still lacking. Thence, we measured the growth, biomass accumulation, and biomass allocation of the current-age seedlings of Pinus massoniana after selective logging (logging of competitive trees, LCT; logging of inferior trees, LIT; and unselective logging, CK), and established structural equation models (SEMs) among stand spatial structure characteristic indexes, environmental factors, and biomass allocation of organs. The mingling index (M), uniform angle index (W), opening degree (O), soil organic carbon (SOC), soil available nitrogen (SAN), soil available phosphorus (SAP), soil available potassium (SAK), and soil bulk density (SBD) have significantly increased (p＜0.05), while the competition index (CI) and neighborhood comparison (U) have significantly decreased after logging (p＜0.05). After the LCT, seedlings branch biomass was improved, and ground-diameter, crown-root ratio, and seedling quality index were increased. More biomass was allocated to foliage and roots by increasing height and height-diameter ratio under the LIT. In the CK, increasing stem biomass would help the seedlings to absorb and utilize more light. The Pearson correlation showed that biomass allocation of organs was independent and seedlings took the strategies of the heterogeneous adaptation and growth, thereby resulting in the separation of the allocation patterns among the organs. The CI was the main factor to biomass allocation with the redundancy analysis (RDA). The environmental factors had direct effects on biomass allocation of organs, while the stand spatial structure characteristic indexes had indirect effects on the biomass allocation based on SEMs through environmental factors. In summary, the LCT has significant and indirect effects SOC, SAN, and SBD by reducing the CI of the stand on the regeneration and growth of seedlings, which was of great significance to the sustainable development of the forest stand of P. massoniana.